Novel non-mulberry silk fibroin nanoparticles with enhanced activity as potential candidate in nanocarrier mediated delivery system. Issue 15 (3rd March 2020) - Baruah, Rashmi Rekha; Chandra Kalita, Mohan; Devi, Dipali
Abstract : Novel Antheraea assamensis silk fibroin nanoparticles (AA-SFNps) exhibiting enhanced activity as doxorubicin hydrochloride (DOX) loaded nanocarriers for future drug delivery applications. Abstract : Silk fibroin (SF) is well known for its excellent biocompatible properties facilitating its application in the field of biomedical engineering through different biomaterial fabrications in the recent era. Here in this study, novel nanoparticles from non-mulberry SF of Antheraea assamensis were fabricated, characterized and evaluated for its applicability as nanocarrier. Fabricated nanoparticles were initially compared with prevailing SF nanoparticles from Bombyx mori . Fabricated A. assamensis silk fibroin nanoparticles (AA-SFNps) were found to be lesser in size (80–300 nm in diameter) than B. mori silk fibroin nanoparticles (BM-SFNps) (120–500 nm in diameter). When checked for stability, AA-SFNps were found to be more stable than BM-SFNps in biological media. FTIR and XRD studies revealed persistence of structural properties even after fabrication. TGA and DSC studies showed AA-SFNps to be thermally more stable than BM-SFNps without any cytotoxicity (MTT assay). On loading with model drug Doxorubicin hydrochloride (DOX), AA-SFNps exhibited an encapsulation efficiency of 94.47% with 11.81% loading of the anticancer drug. Cumulative release study revealed highest percentage release of DOX (42.1 ± 0.4%) at pH 5.2 on day 7 in comparison to pH 7.4 and 8.0. Sustained release profile of the DOX loaded AA-SFNps (AA-SFNps-DOX) was clearly reflected and it was found to be highly cytotoxic against triple negative MDA-MB-231 cells in comparison to free DOX at different time points. Overall, this study showed the efficacy of the AA-SFNps as a nanocarrier for future drug delivery applications.